Laser engineered net shaping of quasi-continuous network microstructural TiB reinforced titanium matrix bulk composites: Microstructure and wear performance. (1st February 2018) - Hu, Yingbin; Ning, Fuda; Wang, Hui; Cong, Weilong; Zhao, Bo
Graphical abstract: Highlights: A three-dimensional quasi-continuous network (3DQCN) microstructure was formed. The laser power played an important role in forming the 3DQCN microstructure. The formation mechanisms of the 3DQCN microstructure were investigated. The effects on workpiece wear performance were studied. Abstract: Titanium (Ti) and its alloys have been successfully applied to the aeronautical and biomedical industries. However, their poor tribological properties restrict their fields of applications under severe wear conditions. Facing to these challenges, this study investigated TiB reinforced Ti matrix composites (TiB-TMCs), fabricated by in-situ laser engineered net shaping (LENS) process, through analyzing parts quality, microstructure formation mechanisms, microstructure characterizations, and workpiece wear performance. At high B content areas (original B particle locations), reaction between Ti and B particles took place, generating flower-like microstructure. At low B content areas, eutectic TiB nanofibers contacted with each other with the formation of crosslinking microstructure. The crosslinking microstructural TiB aggregated and connected at the boundaries of Ti grains, forming a three-dimensional quasi-continuous network microstructure. The results show that compared with commercially pure Ti bulk parts, the TiB-TMCs exhibited superior wear performance (i.e. indentation wear resistance and friction wear resistance) due to the present of TiB reinforcement and the innovative microstructures formed inside TiB-TMCs. In addition, the qualities of the fabricated parts were improved with fewer interior defects by optimizing laser power, thus rendering better wear performance.